IMPROVEMENT OF MATHEMATICAL ABILITY THROUGH DISCOURSE TEACHING WITH MATHEMATICAL BELT LINE AT THE FOURTH GRADE OF ELEMENTARY SCHOOL - Pratiwi, Inne Marthyane; Herman, Tatang; Jupri, Al (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This study was done in response to Farida’s finding (Farida, 2015) about the analysis of errors made by the eighth-grade students of junior high school in one of the schools in solving mathematical story problems which showed that their mathematical ability was still low. The students’ low ability in solving mathematical story problems was caused by their low ability in understanding mathematics. This aim was aimed at describing data on students’ ability in understanding mathematics as the result of the implementation of discourse teaching with Mathematical Bet Line strategy. This study was a quasi-experiment with a nonequivalent control group design. The sample consisted of all students of the fourth-grade in one school in Kuningan district, Kuningan regency. The study used mathematical ability test based on indicators developed by Skemp (1976). The statistical analysis used in this study was independent sample t-test. The result showed that the improvement in the students’ mathematical understanding ability of those who learned through discourse teaching with Mathematical Bet Line strategy was better than that of those who learned through Direct Instruction in the topic criterion fraction.The improvement in mathematical ability was shown by N-gain of 0.67, falling in the mediumcriterion.